Snakebite epidemiology in humans and domestic animals across the Terai region in Nepal: a multicluster random survey. Issue 3 (March 2022) - Alcoba, Gabriel; Sharma, Sanjib Kumar; Bolon, Isabelle; Ochoa, Carlos; Babo Martins, Sara; Subedi, Manish; Shah, Bhupendra; Ghimire, Anup; Gignoux, Etienne; Luquero, Francisco; Ruiz de Castañeda, Rafael; Ray, Nicolas; et al.
Summary: Background: Each year, 2 million people worldwide are bitten by snakes, resulting in an estimated 81 000–138 000 deaths. WHO has added snakebite envenoming to the list of neglected tropical diseases, highlighting the need for stronger epidemiological evidence in endemic countries, such as Nepal. Methods: We conducted a cross-sectional survey in villages randomly geospatially selected from aerial images from across the Nepal's Terai lowlands region (excluding towns and cities). We collected data between Nov 30, 2018 and May 7, 2019, and analysed snakebite incidence rates and outcomes in humans and domestic animals. Findings: Among 63 454 human participants living in 13 879 households (249 villages), 166 were bitten by a snake over the previous 12 months; 48·8% were envenomed and 7·8% died. This corresponded to an annual crude incidence rate of 262 snakebites (adjusted incidence of 251·1 [95% CI 201·7–312·6]) and 20 deaths (22·4 [11·9–42·1]) per 100 000 people, extrapolating to 26 749–37 661 yearly bitten people and 2386–3225 deaths. Bitten people had a median age of 30 years (IQR 20–45) and with available data, 64% were female. Children younger than 15 years (n=6; 46%) and females (n=10; 77%) were disproportionately affected among the 13 people who died. The incidence was higher in the Eastern region, and mortality was higher in the Central region. Of 183 949 animals, owners reported 144 snakebites, with an annual incidence rate of 42–202 per 100 000 and mortality of 79–100%, varying by animal type. Spatial and seasonal incidence were similar in humans and in animals. Interpretation: This study provides the first epidemiological estimates of snakebite envenoming in humans and domestic animals across Nepal's Terai lowlands. It was also the first to use a community-based, transdisciplinary, and One Health design. These findings call for a strengthening of preventive measures and better access to life-saving treatments. Funding: Swiss National Science Foundation project 315130_176271 (SNAKE-BYTE).